AICCRA supports four Kenyan universities in co-developing and rolling out ten accredited climate-smart agriculture programs - Nderi, Alex; Ogutu, Elizabeth; Nzuki, Esther; Waswa, Boaz; Gichunge, Karen (2025)
Between 2023 and 2025, AICCRA and four Kenyan universities co-developed ten accredited climate-smart agriculture programs, strengthening institutional capacity and partnerships among academia, government, and industry.